2011
DOI: 10.1080/02755947.2011.572799
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Passive Integrated Transponder Tags in Stream‐Dwelling Rainbow Trout

Abstract: Passive integrated transponder (PIT) tags have been widely used as a tool for various monitoring and research needs, but the retention of PIT tags has rarely been tested in resident salmonids. We quantified the short‐term (≤1 week), annual (1 year), and long‐term (≥1 year) retention rates of PIT tags placed in the peritoneal cavity of small resident rainbow trout Oncorhynchus mykiss in 11 study streams and assessed whether fish size and gender affected tag retention. Short‐term retention rates were at least 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 18 publications
1
35
1
Order By: Relevance
“…The PIT tag shedding rate for this study (five‐month rate = 0.241) was higher than observed in some previous studies (Dieterman & Hoxmeier, ; Ombredane, Baglinière, & Marchand, ), but lower than observed in other assessments (Bateman, Gresswell, & Berger, ; Meyer, High, Gastelecutto, Mamer, & Elle, ). Bateman et al, () observed a range of yearly retention rates from 0.62 to 0.80 in wild cutthroat trout Oncorhynchus clarkii while Ombredane et al, () observed an average PIT tag loss rate in juvenile brown trout of 3.38% seven months after implantation.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The PIT tag shedding rate for this study (five‐month rate = 0.241) was higher than observed in some previous studies (Dieterman & Hoxmeier, ; Ombredane, Baglinière, & Marchand, ), but lower than observed in other assessments (Bateman, Gresswell, & Berger, ; Meyer, High, Gastelecutto, Mamer, & Elle, ). Bateman et al, () observed a range of yearly retention rates from 0.62 to 0.80 in wild cutthroat trout Oncorhynchus clarkii while Ombredane et al, () observed an average PIT tag loss rate in juvenile brown trout of 3.38% seven months after implantation.…”
Section: Discussioncontrasting
confidence: 73%
“…Bateman et al, () observed a range of yearly retention rates from 0.62 to 0.80 in wild cutthroat trout Oncorhynchus clarkii while Ombredane et al, () observed an average PIT tag loss rate in juvenile brown trout of 3.38% seven months after implantation. Meyer et al, () observed a significant difference in retention rates of mature male and female rainbow trout, suggesting that egg expulsion may cause tag loss in salmonids, which has also been reported in other studies (Bateman et al, ). Furthermore, Dieterman and Hoxmeier () reported a 100% PIT tag retention rate when implanted into the dorsal musculature compared with 70% when placed into the body cavity.…”
Section: Discussionsupporting
confidence: 62%
“…Unexpectedly, tag retention rates during the two last and longest periods (days 173-358 and 358-533) of the experiments decreased again to levels close to the rates immediately after tagging. Low PIT tag retention rates of larger fish in studies of other Salmonidae species have been ascribed to tag loss during spawning [2][3][4][5]. As the experiment was ended before fish were ready to spawn, this was not a factor affecting our results.…”
Section: Discussionmentioning
confidence: 80%
“…Despite the wide use of PIT tags in both laboratory experiments, field studies and population monitoring of Atlantic salmon, we are not aware of any published information on long-term retention of PIT tags spanning juvenile to adult life stages. For other species of Salmonidae PIT tag retention rates have been published covering longer time periods and life stages from both fresh water resident [3][4][5] and anadromous [6] populations. Studies of long-term retention (> 1 year) have been exclusively conducted in natural settings, making frequent recaptures to determine temporal trends in retention rates difficult for fresh water resident populations and impossible for anadromous populations during the ocean phase of their life.…”
Section: Introductionmentioning
confidence: 99%
“…Passive integrated transponder (PIT) tags have been reliably used for over a decade in many taxa including small mammals, fish, reptiles, and amphibians (see Gibbons and Andrews, 2004 for an overview). Rates of tag retention vary according to species, life stage, individual size, placement (specific location and direction of tag application), and handler experience (Meyer et al, 2011). Failure to meet the assumption of tag retention can lead to biased population estimates, erroneous conclusions, and thus poor management decisions.…”
mentioning
confidence: 99%